Review of Wayne Schneider, ed. 1999. The Gershwin Style: New Looks at the Music of George Gershwin. New York: Oxford University Press - Schiff, David (Current Musicology, 2000)
This volume, published just after the Gershwin centenary in 1998, already seems to belong to an awkward age of transition in musicology. A number of the book's twelve essays beat the drums for a new approach to Gershwin that would rescue him from the snobbery of high art prejudices, and for a more general attempt by musicologists to engage with popular culture. A look at the program for recent American Musicological Society meetings quickly reveals that the revolution has already happened; pop is everywhere. But Gershwin remains as elusive as ever.